NEED ANALYSIS OF ENGLISH LANGUAGE USED FOR STUDENTS IN HOSPITALITY INDUSTRY DEPARTMENT - Anisa Zahroh Kusuma; Magdad Hatim; Yuspar Uzer (Universitas PGRI Palembang, 2023)
This need analysis research aimed to know the source of information that studentsâ€™ need in the necessities, lacks and wants related to the studentsâ€™ vocational area.Â This study was a qualitative research and the data collected by the primary data of questionnaire to 39 students, teacher interview and the secondary data was the documentation of syllabus. According to Target Situational Analysis (TSA) of students needs in Hospitality Industry Department of Muhammadiyah Vocational High School 3 of Palembang, synchronized with interview and documentation, the students questionnaire revealed the â€œNecessitiesâ€ were 81.5% or slightly high to upgrading their skills, not only for the requirement at school. Students â€œLacksâ€ in learning English for Specifics Purpose were 61.45% because the students lack of vocabulary. And the potential skills that students need according the â€œwantsâ€ in learning English shows that the most wanted skill is, 1) Speaking (80.95%), 2) Listening (80.8%), 3) Reading (75.9%) and lastly, 4) Writing (75%).Â Â Related to the students needs, the students must practice more and aware with the English as the future needs in academic, career and personal interest to become capable and proficient as the communicative skills. This research was tried to discover the information about the potential needs on English for Specifics Purposes for vocational needs.